2017
DOI: 10.1002/cphc.201700447
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Electrocatalysis for Energy Conversion and Synthesis of Organic Molecules

Abstract: Ubiquitous electrochemistry is expected to play a major role for reliable energy supply as well as for production of sustainable fuels and chemicals. The fundamental understanding of organics‐based electrocatalysis in alkaline media at the solid–liquid interface involves complex mechanisms and performance descriptors (from the electrolyte and reaction intermediates), which undermine the roads towards advance and breakthroughs. Here, we review and diagnose recently designed strategies for the electrochemical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 251 publications
1
72
0
1
Order By: Relevance
“…with the smallest overpotential); (iv) suppression of the formation of strongly adsorbed intermediate species. 12,25 We reported the use of "Bromide Anion Exchange" (BAE) method, [29][30][31] a surfactant-free approach, to develop a line-up of Au-Pd-Pt nanocatalysts able to oxidize efficiently glucose at low electrode potentials at various pHs. [32][33][34] It was also shown that monometallic Au enables a selective oxidation of a range of carbohydrates by their anomeric position and even in a cogeneration fuel cell; 13,35 however, it was postulated that the selectivity remained limited to Au that exhibits remarkable catalytic activity [36][37][38] toward aldehydes and hemiacetals oxidation.…”
Section: H426mentioning
confidence: 99%
See 4 more Smart Citations
“…with the smallest overpotential); (iv) suppression of the formation of strongly adsorbed intermediate species. 12,25 We reported the use of "Bromide Anion Exchange" (BAE) method, [29][30][31] a surfactant-free approach, to develop a line-up of Au-Pd-Pt nanocatalysts able to oxidize efficiently glucose at low electrode potentials at various pHs. [32][33][34] It was also shown that monometallic Au enables a selective oxidation of a range of carbohydrates by their anomeric position and even in a cogeneration fuel cell; 13,35 however, it was postulated that the selectivity remained limited to Au that exhibits remarkable catalytic activity [36][37][38] toward aldehydes and hemiacetals oxidation.…”
Section: H426mentioning
confidence: 99%
“…New type of devices so-called "co-generation or co-production" FCs arise from the possibility of reaching efficiently and simultaneously these two goals. 8,9,[11][12][13][14][15] For instance, the current platforms for H 2 production are largely based on fossil fuels (steam methane reforming, coal gasification), and lead to the emission of significant quantities of greenhouse gases (CO 2 and other carbon-based species in addition to the need of high temperatures), which apparently violates our original intention of reducing global warming by the employment of H 2 power. 16 Besides, the organic electrosynthesis is expected to replace, somehow, toxic or hazardous reagents, avoid large quantities of stoichiometric oxidizers and reducers as well as the in situ production of unstable and/or hazardous chemicals, which means that the waste originating from the used reagents is almost negligible.…”
mentioning
confidence: 99%
See 3 more Smart Citations